EU Land Markets and the Common Agricultural Policy - Pavel Ciaian; d'Artis Kancs; Johan Swinnen (Economics and Econometrics Research Institute (EERI), 2010)
Economic theory, as well as empirical findings, suggest that the way in which agricultural support is provided has an influence on land markets, because payments capitalise to some degree into land values, affecting both the sale and rental price of land. The present paper analyses how the income distributional effects and farm restructuring are impacted by the SPS by accounting for entitlement tradability, cross-compliance requirements, different SPS implementation models, and the entitlement stock. Our results suggest that the SPS implication details are highly important: farmers' benefits can range from 100% of the SPS value to a negative policy incidence, and farm structural change may be hindered by the SPS.
Keywords: H22; L11; Q11; Q12; Q15; Q18; P32; R12; 330; Decoupled subsidies; capitalisation; land market; income distributional effects; SPS; structural change